Angiolymphoid Hyperplasia with Eosinophilia Located on the Forehead: A Possible Association with Oral Contraceptive Use? - Nantia-Eleni Theofilou; Paolo Scolozzi; Tommaso Lombardi (MDPI AG, 2019)
Angiolymphoid hyperplasia with eosinophilia (ALHE) is an uncommon benign vasoproliferative tumor characterized by nodules, papules or plaques localized principally in the head and neck region. Histopathological examination reveals hyperplastic blood vessels lined by large endothelial cells, accompanied by an infiltrate of inflammatory cells including eosinophils. The pathogenetic mechanism remains unclear, although different theories have been proposed. Various treatment strategies have been described, but surgery remains the treatment of choice. We describe the case of a young woman with ALHE taking an oral contraceptive pill suggesting a possible etiopathogenetic relationship.